Medical microbiology - Murray, Patrick R. (Mosby/Elsevier, 2009)
The new edition of this popular text presents microbiology in a succinct, easy-to-use, and engaging manner. Clear discussions explain how microbes cause disease in humans, and review the updated vaccines and new antibiotics currently available to treat these diseases. Expert coverage of basic principles, the immune response, laboratory diagnosis, bacteriology, virology, mycology, and parasitology ensures that you'll understand all the facts vital to the practice of medicine today. A revised artwork program illustrates the appearance of disease, simplifying complex information, while text boxes and additional summary tables emphasize essential concepts and learning issues for more efficient exam review. Online access to Student Consult-where you'll find the complete contents of the book, fully searchable...Integration Links to bonus content in other Student Consult titles...updated features for both students and instructors...and much more-further enhances your study and exponentially boosts your reference power.